Screening, isolation and purification of antibacterial agents from marine actinomycetes - Attimarad, Sunil Laxman; Ediga, Gaviraj N; Karigar, Asif Abdulrahiman; Karadi, Ravindra; Chandrashekhar, Nagesh; Shivanna, Chandrashekara (International Current Pharmaceutical Journal, 2012)
As marine environmental conditions are extremely different from terrestrial ones, it is surmised that marine actinomycetes might produce novel bioactive compounds. Hence marine sediments, collected from the coastal areas of Gokharna and Muradeshwara of Karnataka state, were screened Seventeen isolates were obtained on starch-casein agar media by soil dilution technique. However, only six isolates namely ACT-A2, ACT-A3, ACT-A4, ACT-A5, ACT-A7 and ACT-A15 showed significant antibacterial activity against both gram-positive and gram-negative bacteria. Morphological, cultural and biochemical characterization indicated that the isolates belong to Streptomyces genus of Actinomycetes. Further studies were carried out with the most active ACT-A2. Optimization of media, temperature and pH by shake flask fermentation indicated starch-casein, 28°C and 7 to be suitable for ACT-A2. The production of antibiotics began after 24 h, reached maximum at 72 h and maintained at the same level up to 120 h. Ethyl acetate was used to extract antibacterial compounds from the culture filtrate. TLC was done on silica gel using ethyl acetate: methanol (6:4) and direct bioautography has shown the presence of two active substance, one with Rf 0.8 has more activity than the other with Rf 0.4. Further purification is done by column chromatography using a mixture of dicholoromethane and ethyl acetate. The findings from this investigation reveal that the strain ACT-A2 in order exhibited superior antimicrobial activities to other sediment isolates of actinomycetes. DOI: http://dx.doi.org/10.3329/icpj.v1i12.12448 International Current Pharmaceutical Journal 2012, 1(12): 394-402